2020
DOI: 10.1037/tra0000864
|View full text |Cite
|
Sign up to set email alerts
|

Mental health stressors in Israel during the coronavirus pandemic.

Abstract: A survey of 503 Israelis, performed in April 2020, found high levels of anxiety and risk for depression; these mental health issues were associated with several stressors connected with the coronavirus and related policies. However, only a small percentage of the sample received mental health care from a professional, with native-born Israelis less likely than recent immigrants to receive such care. Some possible initiatives based on these findings are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 4 publications
4
39
1
1
Order By: Relevance
“…Because of prolonged countrywide lockdown orders, many people were worried about purchasing enough food and medication, and many suffered financial losses and experienced distress (Pfefferbaum and North, 2020;Shapiro et al, 2020). The sample was composed of 51% females, aged 18-84 (M = 41.6, SD = 16.38), of whom 85% were born in Israel and the rest in "other" countries.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Because of prolonged countrywide lockdown orders, many people were worried about purchasing enough food and medication, and many suffered financial losses and experienced distress (Pfefferbaum and North, 2020;Shapiro et al, 2020). The sample was composed of 51% females, aged 18-84 (M = 41.6, SD = 16.38), of whom 85% were born in Israel and the rest in "other" countries.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…The mental health of general populations during the COVID-19 pandemic has been investigated widely. Since February 2020, data have been published from 32 surveys of symptoms of depression, anxiety, and acute or post-traumatic stress experienced by unselected populations in 13 countries ( Banna et al., 2020 ; Barros et al., 2020 ; Casagrande et al., 2020 ; Dawel et al., 2020 ; Duan et al., 2020 ; Ettman et al., 2020 ; Fisher et al., 2020b ; Fitzpatrick et al., 2020 ; Gao et al., 2020 ; González-Sanguino et al., 2020 ; Gualano et al., 2020 ; Huang and Zhao, 2020a , b; Islam et al., 2020 ; Li and Wang, 2020 ; Liu et al., 2020 ; Moghanibashi-Mansourieh, 2020 ; Naser et al., 2020 ; Ozamiz-Etxebarria et al., 2020 ; Passos et al., 2020 ; Pierce et al., 2020 ; Planchuelo-Gómez et al., 2020 ; Shapiro et al., 2020 ; Shi et al., 2020 ; Smith et al., 2020 ; Twenge and Joiner, 2020 ; Verma and Mishra, 2020 ; Wang et al., 2020 ; Zhang and Ma, 2020 ; Zhao et al., 2020a ; Zhao et al., 2020b ; Zhou et al., 2020 ). The inclusion criteria for most were to be aged at least 18 years and a resident of the country.…”
Section: Introductionmentioning
confidence: 99%
“…All survey instruments included study-specific questions to ascertain demographic characteristics and, in some, to assess being affected by or infected with SARS-CoV-2/COVID-19 or self-appraised impact of public health restrictions ( Banna et al., 2020 ; Dawel et al., 2020 ; Fisher et al., 2020a ; Huang and Zhao, 2020a ; Passos et al., 2020 ; Wang et al., 2020 ). Several measures of depressive symptoms, including the full nine-item Patient Health Questionnaire (PHQ-9) either in its original English-language form ( Dawel et al., 2020 ; Ettman et al., 2020 ; Fisher et al., 2020a ; Naser et al., 2020 ), or in a local language adaptation ( Shi et al., 2020 ), or the short two-item PHQ-2 ( González-Sanguino et al., 2020 ; Gualano et al., 2020 ; Passos et al., 2020 ; Shapiro et al., 2020 ; Twenge and Joiner, 2020 ; Zhao et al., 2020b ) were used. Others used the full ( Huang and Zhao, 2020b ) or short-form ( Fitzpatrick et al., 2020 ) Centre for Epidemiological Studies Depression Scale (CES-D), the 12-item General Health Questionnaire (GHQ-12) ( Li and Wang, 2020 ; Pierce et al., 2020 ), the Beck Depression Inventory ( Smith et al., 2020 ), or the World Health Organization-Five Wellbeing Index ( Dawel et al., 2020 ; Gao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a rise in suicidal tendencies and deaths was associated with the effects of the coronavirus pandemic or lockdown (Buschmann and Tsokos, 2020). The few studies that focused on the Israeli population showed a high prevalence of worry, nervousness and loneliness, and a rise in levels of depression and anxiety during the beginning of COVID-19 Shapiro et al, 2020;Yehudai et al, 2020). These studies highlight loneliness as an important factor affecting the different aspects of current psychological distress, among them stress, financial worries, anxiety and depression levels Palgi et al, 2020;Lipskaya-Velikovsky, 2021).…”
Section: Introductionmentioning
confidence: 99%